A benzo[e]indole[2, 1-b][1, 3]benzooxazine derivative as a highly sensitive CN− sensor by means of UV–visible difference spectroscopy. (May 2021) - Zhu, Yan; Chen, Guo-Guo; Zhang, Zhen-You; Shen, Shi-Li; Ge, Yan-Qing; Cao, Xiao-Qun; Pang, Xian-Hong
Abstract: In this study, a benzo[e]indole[2, 1-b][1, 3]benzooxazine derivative 2-nitro-5a-(2-(2-thiophene)-ethylene)-6, 6-dimethyl-5a, 6-dihydro-12H-benzo[e]indolo[2, 1-b][1, 3]benzooxazi-ne (TEO ) was explored as a sensitive probe for CN − . Unlike conventional spiropyrans that possess a 3 H -benzo[e]indole cation and a 4-nitrophenolate anion in the same conjugated structure, TEO enhances the positive charge of the 3H-benzo[e]indole cation, which considerably improves its sensitivity and reaction speed. UV–visible spectrophotometry was used to detect CN − with a detection limit of 0.1 μM and a rate constant of 0.528s −1 . In this study, TEO probe showed high selectivity and sensitivity to CN − . Therefore, this probe allows overcoming the limitations of prevailing techniques against the S 2− interference. In addition to UV titration for the determination of CN −, we also added fluorescence titration experiments. CN − of 0.1 μM can also be detected by fluorescence titration. Moreover, the probe was successfully used to detect amygdalin content in almonds. Compared with high-performance liquid chromatography (HPLC), this method avoids the complexity of the extraction process and the interference of polar components. Furthermore, the results are consistent with those obtained by the HPLC method. Graphical abstract: TEO was proposed as a highly sensitive CN − probe by UV–visible spectrophotometry. TEO transforms from a closed-loop structure to an open-loop structure in methanol buffer solution, and the conjugate system becomes larger after the switching. After joining the CN −, the pro-nuclear addition reaction took place with TEO, and TEO 's conjugate system was destroyed. CN − was identified by UV spectral changes. As CN − is added the color of the solution changes quickly from orange to light yellow, easily visible to the naked eye. Image 1 Highlights: TEO was proposed as a highly sensitive CN − probe by UV–visible spectrophotometry. The probe showed superior sensitivity and selectivity toward CN − . The minimum detection concentration of the probe was 0.1 μM. The probe only responds to CN − and is not disturbed by S 2− . TEO can be used to detect the content of amygdalin.